Management of Men Diagnosed with Schizophrenia Using a Family Medicine Approach - Putri Nabila Febrianty; Raihan Akbar Darmawan; Azzahra Roudatul Jannah; Winsca Maghfirda Yasya; Dhia Adhi Perwirawati; Maria Selvester Thadeus; Tiwuk Susantiningsih (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Family medicine emphasizes comprehensive and sustainable health care for individuals and families. Objective: This study aimed to identify clinical problems in patients with schizophrenia and their families, and to analyze factors influencing schizophrenia-related problems using a family medicine approach.Methods: Management was conducted using a family-centered approach designed to create comprehensive health conditions encompassing physical, mental, social, and emotional aspects. The intervention encouraged a supportive family environment for healthy living behaviors and increased family awareness of disease prevention and health promotion in schizophrenia. Family coaching and education were delivered using RANGKUL promotional media. Results: Family coaching demonstrated improved family understanding of schizophrenia, indicated by an increase in post-test scores of 50 out of 100 compared with pre-test results. Families showed better recognition of symptoms, treatment goals, and the importance of long-term care and medication adherence. Conclusion: Management of a male patient diagnosed with catatonic schizophrenia can be effectively implemented using a family medicine approach. Key supporting factors included high family enthusiasm, openness in providing information for family assessment, and strong commitment to maintaining the patient’s medication compliance. Complicating factors included the parents’ educational level, limited to junior and senior high school, requiring information delivery in simple language.